in my research work I am sticking with a equation like--
A1*exp(a*x)-A2*exp(-a*x)+A3*exp(-x/A)=0
solving for x
how should i proceed if i don want to solve it numerically..
I mean I need some expression for x. what may be the technique to follow.
well the equation actually has not have only one independent variable actually there are two..
let's see like this A1=f(y)
now,
A1*exp(a*x)-A2*exp(-a*x)+A3*exp(-x/A)=0
is it possible to solve like x=f(y)
like as below
if (y+1)exp(-a*x)=1
then x= -ln(1/(y+1))/a
Thanks to all for helping me to understand